The Influence Of Human Resource Development, Leadership And Organizational Culture On Employee Performance With Work Ethic As An Intervening Variable In The Housing And Regional Office Langkat Regency Settlement - Ferisna Yuliamita Saragih; Kholilul Kholik; Saimara A.M Sebayang (UNIVED Press, 2026)
This research aims to analyze the influence of human resource development, leadership, and organizational culture on employee performance with work ethic as an intervening variable in the Langkat Regency Housing and Settlement Area Office. This study uses a quantitative approach. The population in this study is all employees of the Langkat Regency Housing and Settlement Areas Office which totals 50 people. Because the population is relatively small, the entire population is used as a sample with a total sampling technique, so that the research sample totals 50 respondents. Data was collected through the distribution of questionnaires with a Likert scale and analyzed using the Partial Least Squares-Structural Equation Modeling (PLS-SEM) method with the help of the SmartPLS 3.0 application. The results of the study show that human resource development has a positive and significant effect on work ethic with a coefficient of 0.357 and on employee performance with a coefficient of 0.644. Organizational culture has a positive and significant effect on work ethic with a coefficient of 0.452, but does not have a significant effect on employee performance with a coefficient of 0.049. Work ethic has a positive and significant effect on employee performance with a coefficient of 0.258. Furthermore, leadership does not have a significant effect on work ethic with a coefficient of 0.145, but has a positive and significant effect on employee performance with a coefficient of 0.581. In the indirect influence, organizational culture has a significant effect on employee performance through work ethic with a coefficient of 0.217, and human resource development also has a significant effect on employee performance through work ethic with a coefficient of 0.192. Meanwhile, leadership does not have a significant effect on employee performance through work ethic with a coefficient of 0.138. The R Square value shows that work ethic can be explained by 82.4%, while employee performance can be explained by 87.0% by the research model. This research shows that the development of human resources, leadership, and organizational culture has an important role in improving employee performance, both directly and indirectly through work ethic. Therefore, agencies need to improve human resource development programs, strengthen leadership, and build a good organizational culture to encourage improvement in work ethic and employee performance.